Peran Komunikasi Interpersonal Keluarga: dalam Menjaga Kesehatan Mental Mahasiswa - Nasichah N; Muhammad Javier Aisyar; Raisa Fazila Farsa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the importance of the family's role in supporting and maintaining the mental health of university students who frequently face significant pressures in the modern era. University life, characterized by academic workloads, organizational responsibilities, and social competition, places students among the groups most vulnerable to psychological distress. Using a qualitative approach through a literature review method, this study analyzes how parental support and patterns of communication within the family influence the mental well-being of university students. The findings indicate that the family serves not only as a source of financial and logistical support but also as the primary source of emotional support, helping to reduce students' levels of stress, anxiety, and feelings of insecurity. Open communication, a willingness to listen without judgment, and parental validation of students' emotions are key factors in strengthening students' mental resilience amid the challenges of a rapidly changing society.